2023
DOI: 10.3390/ijms24031899
|View full text |Cite
|
Sign up to set email alerts
|

SOMAscan Proteomics Identifies Novel Plasma Proteins in Amyotrophic Lateral Sclerosis Patients

Abstract: Amyotrophic lateral sclerosis (ALS) is a complex disease characterized by the interplay of genetic and environmental factors for which, despite decades of intense research, diagnosis remains rather delayed, and most therapeutic options fail. Therefore, unravelling other potential pathogenetic mechanisms and searching for reliable markers are high priorities. In the present study, we employ the SOMAscan assay, an aptamer-based proteomic technology, to determine the circulating proteomic profile of ALS patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…In addition, the use of chemical nanoparticle cocktails for capturing trace serum and plasma proteins has recently gained attention [13][14][15]. Moreover, target-based analysis using antibodies and aptamers is also advancing, with services offered by Olink (Uppsala, Sweden) and SomaLogic (Boulder, CO, USA), enabling the simultaneous measurement of thousands of proteins in serum and plasma [16][17][18]. This indicates that various technologies are still under development to broaden the scope of biomarker discovery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of chemical nanoparticle cocktails for capturing trace serum and plasma proteins has recently gained attention [13][14][15]. Moreover, target-based analysis using antibodies and aptamers is also advancing, with services offered by Olink (Uppsala, Sweden) and SomaLogic (Boulder, CO, USA), enabling the simultaneous measurement of thousands of proteins in serum and plasma [16][17][18]. This indicates that various technologies are still under development to broaden the scope of biomarker discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Searching for new immune mediators in ALS progression and prognosis, Picher-Martel V. et al identified a distinct plasma immune profile in sporadic ALS patients, similar to two murine models of ALS, i.e., SOD1 G93A and UBQLN2 P497H ; this was also observed in TDP-43 G348C transgenic mice, and this is involved in adipocyte function and leptin signaling [ 10 ]. Additionally, a SOMAscan proteomic analysis identified 42 proteins whose levels significantly differ between the plasma of 16 ALS patients and eight healthy controls [ 11 ]. Four of these proteins—i.e., TARC/CCL17, TIMP-3, NID1 and NID2—that were significantly upregulated in the patient’s sera, support the existence of a ECM–chemokine interplay in the ALS pathogenesis that may be potentially targeted by therapies.…”
mentioning
confidence: 99%